Variants in LTA, TNF, IL1B and IL10 genes associated with the clinical course of sepsis (2016)
ABSTRACT: he aim of this study was to explore the asso ciation between some SNPs of the TNF, LTA, IL1B and IL10 genes with cytokine concentrations and clinical course in Colombian septic patients. We conducted a cross sectional study to genotype 415 septic patients and 205 patients without sepsis for the SNPs -308(G/A) rs1800629 of TNF; ?252 (G/A) rs909253 of LTA; -511(A/G) rs16944 and ?3953(C/T) rs1143634 of IL1B; and -1082(A/G) rs1800896, -819(C/T) rs1800871 and -592(C/A) rs1800872 of IL10. The association of theses SNPs with the following parameters was evaluated: (1) the presence of sepsis; (2) severity and clinical outcomes; (3) APACHE II and SOFA scores; and (4) procalcitonin, C-reactive protein, tumor necrosis factor, lymphotoxin alpha, interleukin 1 beta and interleukin 10 plasma con centrations. We found an association between the SNP LTA ?252 with the development of sepsis [OR 1.29 (1.00–1.68)]; the SNP IL10 -1082 with sepsis severity [OR 0.53 (0.29–0.97)]; the TNF -308 with mortality [OR 0.33 (0.12–0.95)]; and the IL10 -592 and IL10 -1082 with admission to the intensive care unit (ICU) [OR 3.36(1.57–7.18)] and [OR 0.18 (0.04–0.86)], respectively. None of the SNPs were associated with cytokine levels, procal citonin and C-reactive protein serum concentrations, nor with APACHE II and SOFA scores. Our results suggest that these genetic variants play an important role in the development of sepsis and its clinical course